Rapid and sensitive detection of Salmonella with reduced graphene oxide-carbon nanotube based electrochemical aptasensor - Appaturi, Jimmy Nelson; Pulingam, Thiruchelvi; Thong, Kwai Lin; Muniandy, Shalini; Ahmad, Noraini; Leo, Bey Fen (Elsevier, 2020)
Rapid detection of foodborne pathogens is crucial as ingestion of contaminated food products may endanger human health. Thus, the objective of this study was to develop a biosensor using reduced graphene oxide-carbon nanotubes (rGO-CNT) nanocomposite via the hydrothermal method for accurate and rapid label-free electrochemical detection of pathogenic bacteria such as Salmonella enterica. The rGO-CNT nanocomposite was characterized using Fourier transform infrared spectroscopy, Raman spectroscopy, X-ray diffraction and transmission electron microscopy. The nanocomposite was dropped cast on the glassy carbon electrode and further modified with amino-modified DNA aptamer. The resultant ssDNA/rGO-CNT/GCE aptasensor was then used to detect bacteria by using differential pulse voltammetry (DPV) technique. Synergistic effects of aptasensor was evident through the combination of enhanced electrical properties and facile chemical functionality of both rGO and CNT for the stable interface. Under optimal experimental conditions, the aptasensor could detect S. Typhimurium in a wide linear dynamic range from 101 until 108 cfu mL−1 with a 101 cfu mL−1 of the limit of detection. This aptasensor also showed good sensitivity, selectivity and specificity for the detection of microorganisms. Furthermore, we have successfully applied the aptasensor for S. Typhimurium detection in real food samples. © 2019 Elsevier Inc.